2017
DOI: 10.1103/physrevb.95.085301
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the dimensionality of charge transport in organic field effect transistors

Abstract: Ever since the first experimental investigations of organic field effect transistors (OFETs) the dimensionality of charge transport has alternately been described as two dimensional (2D) and three dimensional (3D). More recently, researchers have turned to an analytical analysis of the temperature-dependent transfer characteristics to classify the dimensionality as either 2D or 3D as well as to determine the disorder of the system, thereby greatly simplifying dimensionality investigations. We applied said anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…Controlling the nanoscale self-assembly of polymer materials is a key issue in various elds such as biomimetic materials [1][2][3][4][5] and exible electronics device science. [6][7][8][9][10] To achieve and improve control, both material synthesis and processing methodology have been developing synergistically, thereby providing molecular design and bottom-up approaches for the simple and precise control of nanostructures. The Langmuir-Blodgett (LB) technique is a notable example of nanoscale assembly using an air-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling the nanoscale self-assembly of polymer materials is a key issue in various elds such as biomimetic materials [1][2][3][4][5] and exible electronics device science. [6][7][8][9][10] To achieve and improve control, both material synthesis and processing methodology have been developing synergistically, thereby providing molecular design and bottom-up approaches for the simple and precise control of nanostructures. The Langmuir-Blodgett (LB) technique is a notable example of nanoscale assembly using an air-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for exciton transport in organic thin films, it is preferable to have a structure that is oriented normal to the π–π stacking direction to ensure optimized charge injection and/or extraction . Similarly, organic FETs (OFETs) are required to have a standing‐up molecular orientation, as opposed to the lying‐down orientation in organic LEDs (OLEDs) or organic PVs (OPVs) . In addition to the above‐described advantage, sequential deposition of different organic molecules allows more complex structures such as multicomponent or multidimensional 2D–organic heterostructures.…”
Section: Fabrication and Physical Properties Of 2d–organic Hybrid Strmentioning
confidence: 99%
“…Furthermore, organic semiconductors can be solution‐processed on any substrate inexpensively and at relatively low temperatures, which is highly advantageous for their scale‐up from fundamental studies to industrial‐level production . Initial examples of developed organic semiconductors include field‐effect transistors (FETs), photodetectors (PDs), photovoltaics (PVs), light‐emitting diodes (LEDs), and so on. In spite of the demonstration of promising prototypes of organic semiconductors, their development and optimization for high‐performance device applications remain a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Charge transport generally occurs at the semiconductor/dielectric interface. In recent years, extensive efforts have been devoted to explore the surface charge transport of organic semiconductors . On the one hand, in bulk crystal‐based FETs, several groups studied the surface carrier properties using air gap as gate insulator .…”
Section: Transistor Applications and Physics Of 2dmcsmentioning
confidence: 99%
“…A pioneering study indicated that sexithiophene FETs sustain the saturation current using the first two MLs. Whereas the film thicknesses of the saturation mobility for pentacene range from the monolayer to 5–6 molecular layers . Therefore, variations in film morphologies can result in dramatic differences in the effective film thicknesses for the saturation mobilities.…”
Section: Transistor Applications and Physics Of 2dmcsmentioning
confidence: 99%